(untitled) (Journal of Bangladesh Institute of Planners, 2016)
In Bangladesh a vital portion of natural river system is supported by south-west coastal zone. Khulna Jessore Drainage Rehabilitation Project was initiated to manage the entire coastal zone but failed drastically. It became a great failure for building embankment around the polder area by trapping water and the consequences are flood, water logging, long term salinity etc. in affected area. To get rid of these consequences, people have taken steps to cut the polders for allowing tidal flow and accumulating alluvium inside the polders. This technique of raising land level is known as Tidal River Management (TRM). As a result, in the long process, the reduction of water logged area and emergence of new land have direct influence on the status and quality of people’s life and livelihood. This impact and consequences are analyzed through this study in Beel Bhaina and its adjacent most affected villages of Agarhati and Bharat Bhaina in Keshabpur Upazila, Jessore. TRM practice impacted positively on settlement and displacement issues, income, communication, business, shrimp sector, water logging problems, but at the same time, created negative impacts on agriculture sector. Some hazards, like salinity, river erosion and draught have become more frequent in the area. JBIP, Vol. 9, 2016 (Printed in April 2018), pp. 43-58